Evaluasi Program Penerimaan Peserta Didik Baru (PPDB) Online Di SMPN 4 Kota Bengkulu Tahun 2021 (Studi Menggunakan Model Evaluasi Context Input Process Product) - Mutia (Manajer Pendididikan, 2023)
The purpose of the study was to analyze the evaluation of the online student acceptance program at the State Junior High School 4 Bengkulu City using the CIPP evaluation model. The research method uses this type of evaluation. Data collection techniques used are interviews and documentation. The results of the study are 1) The results of the context evaluation aim to ensure the acceptance of new students is objective, transparent, accountable, non-discriminatory, and fair 2). The results of the input evaluation are the availability of the committee's SK along with details of their duties, prospective students who register through the city's student admissions website 3). Process evaluation includes registration, selection of new students using an online system, announcements, and re-registration. 4). The results of the product evaluation included 315 students who registered, which were accepted by 288 students.